Facile synthesis of MOF-derived porous spinel zinc manganese oxide/carbon nanorods hybrid materials for supercapacitor application. Issue 16 (November 2018) - Zhu, Zihao; Wang, Zhongbing; Yan, Zhaobin; Zhou, Rongqing; Wang, Zhenpeng; Chen, Chunnian
Abstract: For the past few years, transition metal oxides have attracted significant attention for supercapacitor due to their high theoretical capacity, low costs, and abundant natural reserves. In this work, we present a facile strategy to fabricate spinel zinc manganese oxide/carbon hybrid materials with rod-like structures from mixed-MOFs. Through two-steps calcining the mixed-MOFs constituted by metal ion and 1, 3, 5-Benzenetricarboxylic acid in different condition, the mixed-MOFs have converted to ZnMn2 O4 /carbon nanorods. The 1D rod-like nanostructure inherited from the MOFs was preserved intact during the process. Due to the porous 1D nanostructure and synergistic effect between the transition metal oxide and carbon, the specific capacitance of hybrid materials reaches to 589 F g −1 at 1 A g −1 within the potential window of 0–1.2 V. Meanwhile, the hybrid materials display superior capacitive behavior at high current density (278 F g −1 at 20 A g −1 ) and outstanding cycling stability (98.1% retention after 2000 cycles at 10 A g −1 ). The results imply that the MOFs-derived hybrid materials could be potential electrode materials.